Internal and external determinants of corporate social responsibility practices in multinational enterprise subsidiaries in developing countries: Evidence from Ethiopia - Tolossa Fufa Gulema; Yadessa Tadesse Roba (Future Business Journal, 2021)
The purpose of the study is to investigate the internal drivers and external determinants of corporate social responsibility (CSR) strategies practiced by multinational enterprises' (MNEs) using institutional theory and the resource-based view. We propose that MNEs' local business orientations and political behaviors are highly related to firms' CSR selection as internal and external determinants, respectively, and we integrate the actual CSR practices from different characteristics to exploring and exploiting strategies. A multiple regression analysis was conducted by using survey data collected from MNE subsidiaries operating in Ethiopia. We found that firms who are oriented to raise competitiveness with collaborative attitudes toward host governments seek more exploring CSR practices. On the other hand, firms' local orientation that is to build legitimacy with accommodative attitudes toward host governments has positive relations with exploiting CSR practices. Furthermore, contrary to the expectation the result revealed that exploiting CSR practices are positively related to both orientations, which implies that traditional CSR practices are treated fundamentally of importance in developing countries.
Keywords: 650; Competitive advantage; CSR; Exploiting; Exploring; Institutional theory; Legitimacy; MNE; Resource-based View